Endoscopic Mucosal Resection: Early Experience in British Columbia. (2010) - Brahmania, Mayur; Lam, Eric; Telford, Jennifer; Enns, Robert
Abstract : BACKGROUND: Endoscopic mucosal resection (EMR) has been proposed as a primary method of managing patients with dysplasia- or mucosal-based cancers of the esophagus. OBJECTIVES: To evaluate the use of EMR for the treatment of Barrett's esophagus with dysplasia or early adenocarcinoma, assessing efficacy, complication rates and long-term outcomes. METHODS: All patients who underwent EMR at St Paul's Hospital (Vancouver, British Columbia) were reviewed. Eligible patients were assessed with aggressive biopsy protocols. Detected cancers were staged with both endoscopic ultrasound imaging and computed tomography. Appropriate patients were offered EMR using a commercially available mucosectomy device. EMR was repeated at six- to eight-week intervals until complete. Patients with less than one year of follow-up or who were undergoing other ablative methods were excluded. RESULTS: Twenty-two patients (all men) with a mean (± SD) age of 67±10.6 years were identified. The mean duration of gastroesophageal reflux disease was 17 years (range four to 40 years) and all were receiving proton pump inhibitor therapy. The mean length of Barrett's esophagus was 5.5±3.5 cm. One patient had no dysplasia (isolated nodule), three had low-grade dysplasia, 15 had high-grade dysplasia (HGD) and three had adenocarcinoma. A mean of 1.7±0.83 endoscopic sessions were performed, with a mean of 6±5.4 sections removed. Following EMR, three patients developed strictures; two of these patients had pre-existing strictures and the third required two dilations, which resolved his symptoms. There were no other complications. Three patients underwent esophagectomy. Two had adenocarcinoma or HGD in a pre-existing stricture. The third patient had an adenocarcinoma not amenable to EMR. One patient with a long segment of Barrett's esophagus underwent radiofrequency ablation. At a median follow-up of two years (range one to three years), the remaining 18 patients (82%) had no evidence of HGD or cancer. CONCLUSION: Most patients with esophageal dysplasia can be managed with EMR. Individuals with pre-existing strictures require other endoscopic and/or surgical methods to manage their dysplasia or adenocarcinoma.